1978
DOI: 10.1346/ccmn.1978.0260403
|View full text |Cite
|
Sign up to set email alerts
|

The I.R. Spectra of Dimethyl Sulfoxide Adsorbed on Several Cation-Substituted Montmorillonites

Abstract: Abstract--The i.r. spectra (4000-1200 cm 1) are obtained for several homoionic montmorillonite films on which various amounts of dimethyl sulfoxide (DMSO) were adsorbed. Analyses of these spectra indicate that H-and natural-montmorillonite-DMSO complexes contain an intercalated layer of physisorbed DMSO while transition metal cation substitutedmontmorillonite-DMSO complexes possess both physi-and chemisorbed DMSO in their interlamellar spaces. The latter species involve coordination of DMSO molecules with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Although the DMSO-montmorillonite complexes have not been studied by IR spectrometry in this paper, previous works showed that the DMSO molecules interact with the interlayer cation through the oxygen atom of the sulfoxide group (25,26). …”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…Although the DMSO-montmorillonite complexes have not been studied by IR spectrometry in this paper, previous works showed that the DMSO molecules interact with the interlayer cation through the oxygen atom of the sulfoxide group (25,26). …”
Section: Spectroscopic Studiesmentioning
confidence: 99%
“…The transport of organic contaminants through porous media, and the computer modeling of that transport, are of great importance for the prediction of groundwater quality at present (1). Germane to this is the characterization of interactions between mineral surfaces and organic compounds that are implicated as environmental contaminants (2)(3)(4). Through the use of Fourier transform infrared (FT-IR) spectroscopy, the mechanism of an organo-mineral sorption interaction can be determined by an analysis of the direction and magnitude of band shifts and intensity variations when the spectrum of the organic compound is compared against that of the organo-mineral complex (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…[ 18,19 ] Weak but well‐pronounced bands at 2920 and 3010 cm −1 (Figure 3a) are caused by symmetrical and asymmetrical stretching vibrations of CH bonds in DMSO molecules. [ 20 ]…”
Section: Resultsmentioning
confidence: 99%